An analysis of Irish bribery law - Higgins, Imelda (Trinity College (Dublin, Ireland). School of Law, 2015)
The bribery offences are a much neglected area of law, both from an academic and from a practical perspective. Although the existing statutory offences can trace their origins to the dawn of the twentieth century, there has been no substantive academic attempt to analyse those offences in order to determine their precise contours and scope or to assess whether they meet the needs of a modern bribery law. This thesis remedies these lacunae, focusing on the bribery offences contained in the Prevention of Corruption Act 1906, as amended. In particular it considers whether the agent principal model underlying the 1906 Act is capable of meeting the needs of a modern bribery law and, to the extent that it is not, whether those needs could be more effectively met through reliance on the broader breach of duty model of bribery. For the purposes of analysing the bribery offences and determining the requirements of a modern bribery law, this thesis relies on two primary sources. The first is the reports published by the Tribunals of Inquiry established, towards the end of the last century, to inquire into possible instances of political corruption. These reports run to thousands of pages in length and, in the absence of written case-law, comprise the only comprehensive existing source of information on the typologies of Irish bribery. Like the bribery offences themselves, the Tribunal’s reports have been largely ignored by the academic community.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin